Description of the male imago of Paracloeodes eurybranchus Lugo-Ortiz & McCafferty 1996 (Ephemeroptera: Baetidae) - Emmerich, Daniel; Molineri, Carlos (Zootaxa, 2020)
Paracloeodes Day 1955 is represented in America by 22 species, sixteen of them are present in South America (Cruz et al. 2018b). The systematic of the genus is mainly based on nymphs (Nieto & Salles 2006; Emmerich & Nieto 2009; Lima et al. 2010; Cruz et al. 2017) but the association of both stages was recognized to improve the taxonomy of the genus (Cruz et al. 2018a, b). All species are known from the nymphal stage, eleven of them are known from male adults. Paracloeodes eurybranchus is known from nymphs and female adults from Argentina and Brazil. We here describe the male imago and give some additional data for the female imago. The nymphs were collected in small pools on the banks of Los Sauces river. The entire river has a sandy substrate. Along with them, nymphs of Americabaetis alphus Lugo-Ortiz & McCafferty 1996 were also collected.